Bahasa Inggris - Kamarudin, Kamarudin (State Islamic University of Datokarama Palu, 2022)
This paper discusses the meaning of jihad in Islam. Jihad is one of the most discussed themes in the hadith of the Prophet. This fact shows the urgency of the term jihad in the history of the development of Islamic law. The understanding of jihad among Muslims varies, and its implementation varies among Muslims. This study discusses the implementation of jihad at the time of the Prophet's hadith. This study uses a descriptive literature research method using a text study method that examines all hadith texts about jihad. Then the author also conducted a comparative study between the opinions of scholars, both hadith scholars, commentators, and other scholars. The hadith about jihad that is meticulous is not a hadith with the status of a mutawatir hadith but is a hadith that has the status of a hadith. However, all the hadiths studied are authentic hadiths, both from the aspect of the sanad and from the aspect of the eye. The results of this study are expected to provide a correct understanding so that when implementing the hadith about jihad according to its objectives and not only understood in the form of war. Jihad is also understood as a form of non-physical struggle such as jihad against poverty, ignorance, injustice, and doing good to both parents.